Hopf Bifurcation for a Model of HIV Infection of CD4+ T Cells with Virus Released Delay - Jun-Yuan Yang; Xiao-Yan Wang; Xue-Zhi Li (Discrete Dynamics in Nature and Society)
A viral model of HIV infection of CD4+ T-cells with virus released period is formulated, and the effect of this released period on the stability of the equilibria is investigated. It is shown that the introduction of the viral released period can destabilize the system, and the period solution may arise. The direction and stability of the Hopf bifurcation are also discussed. Numerical simulations are presented to illustrate the results.